2023
DOI: 10.36227/techrxiv.21975476.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adapting to progressive paralysis: A tongue-brain hybrid robot interface for individuals with amyotrophic lateral sclerosis

Abstract: <p>Individuals suffering from progressive neuromuscular diseases gradually lose all muscle control and therefore are forced to repeatedly adapt to new control interface technologies to maintain some level of independence. Accordingly, the ideal interface technology should adapt to the progression of paralysis. We propose an adaptive tongue-brain hybrid interface framework for the three-dimensional control of a robotic arm. The interface was tested with able-bodied individuals and individuals with amyotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(23 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…The experiments with healthy participants showed the advantage of combining tongue-and brain signals if the user can no longer use the full ITCI. It was observed that each subsystem achieved slightly worse performance compared to the prior subsystem (4-34% increase in task completion times), but that all performed significantly faster than the full BMI [166]. The full BMI used much longer time idle in a control mode compared to the other subsystems where the ITCI was used to activate the robot, which highlights the importance of at least one robust and time-continuous control signal.…”
Section: Main Findingsmentioning
confidence: 97%
See 4 more Smart Citations
“…The experiments with healthy participants showed the advantage of combining tongue-and brain signals if the user can no longer use the full ITCI. It was observed that each subsystem achieved slightly worse performance compared to the prior subsystem (4-34% increase in task completion times), but that all performed significantly faster than the full BMI [166]. The full BMI used much longer time idle in a control mode compared to the other subsystems where the ITCI was used to activate the robot, which highlights the importance of at least one robust and time-continuous control signal.…”
Section: Main Findingsmentioning
confidence: 97%
“…The bar plots show the average time spend across the four trials and ten subjects on days 1 to 3 (from left to right) for each subsystem. (adapted from [166]) on day two. The second participant performed better with the full BMI, but worse with full ITCI and hybrid subsystem compared to participant one.…”
Section: Study Imentioning
confidence: 99%
See 3 more Smart Citations